Nilai-Nilai Moral dalam Film “Sang Pemimpi” - Lidia Putri; Jamhari Jamhari; Zulhelmi Zulhelmi (Aqlania, 2022)
This study aims to discuss the moral values ​​contained in the film "The Dreamer" by using semiotic analysis. Semiotic analysis was chosen because it is a field of study that is very relevant to analyzing the structure of a film. This research is library research with a qualitative approach. Sources of data in this study consisted of primary data and secondary data. Primary data were obtained from film footage and dialogues containing elements of moral values ​​in the film "The Dreamer". While secondary data was obtained from books, journals, and articles that support the research material. Data collection uses observation and documentation techniques. Data analysis used the semiotic analysis of Roland Barthes. The results showed that in the film "The Dreamer" there are moral values ​​that can be known, including the relationship between humans and God (be kind to God), the relationship between humans and oneself which includes studying, working hard, and being responsible and human relationships with others. other human beings, namely the value of tolerance, helping others, and caring.